1998
DOI: 10.1021/jf9706235
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine, Deethylatrazine, and Deisopropylatrazine Persistence Measured in Groundwater in Situ under Low-Oxygen Conditions

Abstract: The degradation of atrazine [2-chloro-4-(ethylamino)-6-isopropylamino-1,3,5-triazine], deethylatrazine [DEA; 2-amino-4-chloro-6-(isopropylamino)-1,3,5-triazine], and deisopropylatrazine [DIA; 2-amino-4-chloro-6-(ethylamino)-1,3,5-triazine] was assessed under limited oxygen conditions using in situ microcosms. Denitrification was induced in a shallow sand and gravel aquifer to measure the potential for degradation of atrazine, DEA, and DIA under low-O 2 conditions. The dissolved oxygen content decreased from 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…For example, atrazine, simazine and oxadixyl have all been withdrawn from use in the EU for some years yet continue to be routinely detected in groundwater. For atrazine there is long-established evidence that it may be very persistent under conditions of limited oxygen (Papiernik andSpalding 1998, Schwab et al 2006) and in the unsaturated zone below the soil zone where remobilisation is possible (Kruger et al 1993, Jablonowski et al 2009). For oxadixyl the soil half-life is currently commonly given as 60 to 90 days (Wightwick et al 2010).…”
Section: Controls and Mechanismsmentioning
confidence: 99%
“…For example, atrazine, simazine and oxadixyl have all been withdrawn from use in the EU for some years yet continue to be routinely detected in groundwater. For atrazine there is long-established evidence that it may be very persistent under conditions of limited oxygen (Papiernik andSpalding 1998, Schwab et al 2006) and in the unsaturated zone below the soil zone where remobilisation is possible (Kruger et al 1993, Jablonowski et al 2009). For oxadixyl the soil half-life is currently commonly given as 60 to 90 days (Wightwick et al 2010).…”
Section: Controls and Mechanismsmentioning
confidence: 99%
“…As one of the most heavily used herbicides in the United States, atrazine can be present in parts per million in agricultural runoffs (3), which exceeds the U.S. Environmental Protection Agency's maximum allowable contaminant level of 3 ppb in ground and surface waters (13). Atrazine is persistent in soil (34) and was once considered nontoxic to animals. However, recent studies have shown that atrazine causes sexual abnormalities in frogs (21,22,50), reduced testosterone production in rats (53), and elevated levels of prostate cancer in workers at an atrazinemanufacturing factory (45).…”
mentioning
confidence: 99%
“…Atrazine, a widely used selective herbicide for the control of annual grasses and broadleaved weeds, has often been found in drinking water, and therefore, they are a potential threat for the public health [13][14][15][16]. The European Community has established maximum residue level for residues of this herbicide in wine grapes in 50 μg L -1 .…”
Section: Pesticide Residues Detectionmentioning
confidence: 99%